2013
DOI: 10.1128/aem.00982-13
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Dependent Augmentation of Tight-Junction Barrier Function in Human Primary Epidermal Keratinocytes by Lactobacillus and Bifidobacterium Lysates

Abstract: In this study, we investigated whether probiotic lysates can modify the tight-junction function of human primary keratinocytes. The keratinocytes were grown on cell culture inserts and treated with lysates from Bifidobacterium longum, Lactobacillus plantarum, Lactobacillus reuteri, Lactobacillus fermentum, or Lactobacillus rhamnosus GG. With the exception of L. fermentum (which decreased cell viability), all strains markedly enhanced tight-junction barrier function within 24 h, as assessed by measurements of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(99 citation statements)
references
References 35 publications
4
92
0
3
Order By: Relevance
“…Similarly, both Bifidobacterium longum and LGG have been shown to induce the upregulation of claudin-1, ZO-1, and occludin protein levels in keratinocytes (185). Intriguingly, the in vitro increase in keratinocyte transepithelial electrical resistance (TER) induced by a B. longum lysate, but not by an L. rhamnosus GG lysate, was abrogated in the presence of a TLR2-neutralizing antibody, suggesting that these bacteria act on different pathways to influence tight junction molecule expression (185). An in vivo infectious model recently demonstrated that a defined mixture of 33 probiotic bacterial strains pre- vented the Salmonella enterica serovar Typhimurium-induced disruption of ZO-1 and claudin-1 in mice and ameliorated disease severity (191).…”
Section: Other Mechanisms Of Action Of Beneficial Microbes and Probiomentioning
confidence: 96%
See 2 more Smart Citations
“…Similarly, both Bifidobacterium longum and LGG have been shown to induce the upregulation of claudin-1, ZO-1, and occludin protein levels in keratinocytes (185). Intriguingly, the in vitro increase in keratinocyte transepithelial electrical resistance (TER) induced by a B. longum lysate, but not by an L. rhamnosus GG lysate, was abrogated in the presence of a TLR2-neutralizing antibody, suggesting that these bacteria act on different pathways to influence tight junction molecule expression (185). An in vivo infectious model recently demonstrated that a defined mixture of 33 probiotic bacterial strains pre- vented the Salmonella enterica serovar Typhimurium-induced disruption of ZO-1 and claudin-1 in mice and ameliorated disease severity (191).…”
Section: Other Mechanisms Of Action Of Beneficial Microbes and Probiomentioning
confidence: 96%
“…The probiotic yeast S. boulardii increases the expression of ZO-1 in T84 cells (186) and has been associated with decreased intestinal permeability in numerous studies (155,(187)(188)(189)(190). Similarly, both Bifidobacterium longum and LGG have been shown to induce the upregulation of claudin-1, ZO-1, and occludin protein levels in keratinocytes (185). Intriguingly, the in vitro increase in keratinocyte transepithelial electrical resistance (TER) induced by a B. longum lysate, but not by an L. rhamnosus GG lysate, was abrogated in the presence of a TLR2-neutralizing antibody, suggesting that these bacteria act on different pathways to influence tight junction molecule expression (185).…”
Section: Other Mechanisms Of Action Of Beneficial Microbes and Probiomentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, administering during pregnancy and early infancy can reduce the risk of eczema developing [20]. More recently, topical application of probiotics and bacterial composites such as the cellular wall, its metabolites and dead bacteria has also been shown to produce certain immunity responses in the skin and to improve and reinforce the skin barrier [23][24][25].In cases of AD selective defects exist in the expression of the multiple genes which codify the corneal layer of the skin, including the filaggrin or the loricrin which only show 2% of the normal level, with structural alterations and a reduction in the corneocytes and the intercellular lipids. As a result, the whole process of terminal differentiation of the keratinocytes (cytoplasmic compaction, cornification and the release of lipids) necessary for the establishment of the barrier function is defective [37].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, non-viable bacterial derivatives have been shown to exert antimicrobial and immunomodulating action and can elicit certain immune responses on the skin and improve skin barrier functions [23]. It has been found that the application of lysates of probiotic bacteria, such as the Lactobacillus or Bifidobacterium species, on in vitro models increase the barrier function through the modulation of tight-junction protein components and decrease skin reactivity, the release of cytokines and signs of inflammation [24,25]. In addition, trials in healthy volunteers have shown that topical application of bacterial lysates in the form of a cream strengthens the barrier function and decreases skin dryness [25].…”
Section: Introductionmentioning
confidence: 99%